2014
DOI: 10.1371/journal.pone.0096400
|View full text |Cite
|
Sign up to set email alerts
|

Increased Na+/Ca2+ Exchanger Expression/Activity Constitutes a Point of Inflection in the Progression to Heart Failure of Hypertensive Rats

Abstract: Spontaneously hypertensive rat (SHR) constitutes a genetic model widely used to study the natural evolution of hypertensive heart disease. Ca2+-handling alterations are known to occur in SHR. However, the putative modifications of Ca2+-handling proteins during the progression to heart failure (HF) are not well established. Moreover, the role of apoptosis in SHR is controversial. We investigated intracellular Ca2+, Ca2+-handling proteins and apoptosis in SHR vs. control Wistar rats (W) from 3 to 15 months (mo).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
2
15
2
4
Order By: Relevance
“…Notably, no functional difference in Na + /Ca 2+ current density was detected between HHR and NHR cardiomyocytes. This contrasts with previous experimental demonstration of Na + /Ca 2+ exchanger upregulation as a key process in transition to failure in HFrEF . These findings also differ from observations made in a setting of diastolic dysfunction where the primary insult is acute renal intervention (nephrectomy) and cardiomyocyte systolic Ca 2+ levels and contractility are unchanged .…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Notably, no functional difference in Na + /Ca 2+ current density was detected between HHR and NHR cardiomyocytes. This contrasts with previous experimental demonstration of Na + /Ca 2+ exchanger upregulation as a key process in transition to failure in HFrEF . These findings also differ from observations made in a setting of diastolic dysfunction where the primary insult is acute renal intervention (nephrectomy) and cardiomyocyte systolic Ca 2+ levels and contractility are unchanged .…”
Section: Discussioncontrasting
confidence: 96%
“…There was no evidence of HHR‐specific low‐voltage activated currents (absence of inflexion in current plots from −115 and −90 mV holding potentials) (Figure ). Capacity for Ca 2+ flux via the Na + /Ca 2+ exchanger was examined electrophysiologically, as this transporter upregulation is implicated in arrhythmogenicity . In forward mode operation (ie, Ca 2+ extrusion, inward current, from −90 mV) and reverse mode operation (to +40 mV), the I‐NCX densities (pA/pF) were not different for NHR and HHR (Figure D through F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27) Specifically, impaired SERCA2a function and enhanced Na + /Ca 2+ exchanger (NCX) activity have been proposed as causes of reduced SR Ca 2+ load in HF. 28,29) Moreover, the role of pathological diastolic SR Ca 2+ leak via RyR2 has been recognized as an important contributor to the altered Ca 2+ handling in HF. 30,31) Similarly, rats with post-MI HF in our study showed a significant reduction in SERCA2a while the content of NCX1 was markedly increased.…”
Section: Discussionmentioning
confidence: 99%
“…B and C ) (Rodriguez et al . ). Indeed, partial NCX inhibition restores Ca 2+ signalling in myocytes from failing hearts (Hobai et al .…”
Section: Introductionmentioning
confidence: 97%